2018
DOI: 10.1021/acscombsci.8b00042
|View full text |Cite
|
Sign up to set email alerts
|

Development of Biphasic Formulations for Use in Electrowetting-Based Liquid Lenses with a High Refractive Index Difference

Abstract: Commercial electrowetting-based liquid lenses are optical devices containing two immiscible liquids as an optical medium. The first phase is a droplet of a high refractive index oil phase placed in a ring-shaped chassis. The second phase is electrically conductive and has a similar density over a wide temperature range. Droplet curvature and refractive index difference of two liquids determine the optical strength of the lens. Liquid lenses take advantage of the electrowetting effect, which induces a change of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Electrowetting at the liquid|liquid interface has found notable applications in commercial optofluidic devices, such as liquid lenses. , The latter are optical devices containing two immiscible liquids which serve as an optical medium. In most cases, the electrolytically conducting phase is an aqueous electrolyte and the insulating phase is an organic solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Electrowetting at the liquid|liquid interface has found notable applications in commercial optofluidic devices, such as liquid lenses. , The latter are optical devices containing two immiscible liquids which serve as an optical medium. In most cases, the electrolytically conducting phase is an aqueous electrolyte and the insulating phase is an organic solvent.…”
Section: Resultsmentioning
confidence: 99%
“…This may substantially increase the lens response time. To address this issue, we formulated a glycol conductive liquid with the same weight fraction concentration as the conductive liquid mentioned in the article (the propane-1,3-diol containing 1 w% TBAC) and found that the viscosity could be reduced to 18.43 cP, which is not yet commercially required (<10 cP), 56 but the reduction in viscosity is significant. Using glycol formulation as a conductive liquid is expected to improve the response time.…”
Section: Discussionmentioning
confidence: 99%
“…For formulating conductive and insulating liquids for electrowetting liquid lenses, we have some requirements for the properties of these biphasic liquids. 56 The biphasic liquids must be immiscible, and their densities need to match. At the same time, the higher the difference between their refractive indices, the better.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations